(untitled) (Palimpsesto, 2022)
Exploring the history of knowledge through the tools of the intellectual history, we recover some contributions from Foucaultian archeology and genealogy to analyses one segment of the history of the philosophy that became institutional in Argentina. We deal with the journal Verbum, published by the Student Center of the Faculty of Philosophy and Letters of the Buenos Aires University between 1912 and 1948. Thought Verbum we observe how the definitions of academic philosophy in Argentina in those first years have derived from a permanent and tense game of affirmations and exclusions. Theoretical elements converge in it with institutional aspects. The climate of the University Reform invited the actors to think about the university, but it supposed, also, to think about the knowledge and vice versa. In this interwave we practice a complex historization, attentive to the ruptures and the particularities of the development of philosophical knowledge in this context.